Effect of Lifestyle and Gynecological Oncology Nursing Interventions on Quality of Life Improvement: A Systematic Review and Meta-Analysis - Huang, Ling (Clinical and experimental obstetrics & gynecology, 2025)
Background: Gynecologic cancer refers to a variety of malignancies that originate in the reproductive organs of women, including the cervix, ovaries (epithelial and germ cell), uterus (endometrial or corpus as well as sarcoma), vagina, and vulva. Gynecologic oncology nursing is a specialized field offering an integrated approach to treating and managing gynecological cancers, addressing their physical and psychological needs. This systematic review and meta-analysis aimed to evaluate the efficacy of lifestyle intervention plus gynecological care on quality-of-life (QoL) outcomes in women with a diagnosis of at least one type of gynecological cancer. Methods: A methodological adherence to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines resulted in 1034 articles being identified following an exhaustive search of electronic databases. A meta-synthesis was conducted using Rev Man for the 10 studies that met all eligibility criteria after screening. Results: Lifestyle interventions showed significant associations with improved QoL outcomes when comparing baseline measurements to those taken six months post-lifestyle intervention (lifestyle: mean difference (MD) = 0.47, 95% confidence interval (95% CI): 0.09 to 0.86), p = 0.02. However, the pooled effect sizes were not statistically significant (lifestyle: MD = 0.77, 95% CI: –3.00 to 4.54), p = 0.69. Nursing interventions showed mixed effects (MD = 0.94, 95% CI: –5.26 to 7.14), p = 0.77 and no statistically significant improvement in QoL compared to control groups. Sensitivity analysis indicated potential publication bias. Nonetheless, most papers exhibited a minimal risk of bias. Significant heterogeneity was also seen in pooled analyses, possibly indicating variations in study populations, intervention types, and outcome measures. Conclusions: This study suggests lifestyle interventions can improve the QoL in gynecological cancer patients. However, oncology nursing interventions show inconsistent effects, with no significant improvement in the pooled analysis. Future research should standardize interventions to improve understanding of their impact. Registration: The study has been registered on https://www.crd.york.ac.uk/prospero/ (registration number: CRD42024617625).